Clinical dissection of early onset absence epilepsy in children and prognostic implications. Issue 10 (27th August 2013) - Agostinelli, Sergio; Accorsi, Patrizia; Beccaria, Francesca; Belcastro, Vincenzo; Canevini, Maria Paola; Capovilla, Giuseppe; Cappanera, Silvia; Bernardina, Bernardo Dalla; Darra, Francesca; Gaudio, Luigi Del; Elia, Maurizio; Falsaperla, Raffaele; et al.
Summary Purpose To investigate whether patients with typical absence seizures (TAS) starting in the first 3 years of life, conformed to Panayiotopoulos's definition of childhood absence epilepsy (CAE), show different electroclinical course than those not fulfilling CAE criteria. Methods In this multicenter retrospective study, we choose a fixed duration follow‐up of 36 months to examine the electroclinical course of epilepsy in all children with TAS starting before 3 years of age. The probands who fulfilled Panayiotopoulos's criteria for CAE were classified as having pure early onset absence epilepsy (P‐EOAE), whereas those who did not as nonpure EOAE (NP‐EOAE). In addition, these two groups of patients were further stratified according to the number of antiepileptic drugs taken to obtain initial seizure control (mono‐, bi‐, and tritherapy). Key Findings Patients with P‐EOAE (n = 111) showed earlier initial seizure control (p = 0.030) and better seizure‐free survival curve (p = 0.004) than those with NP‐EOAE (n = 77). No mutation in SLC2A1 gene or abnormal neuroimaging was observed in P‐EOAE. Among patients with NP‐EOAE, those receiving tritherapy showed increased risk of structural brain abnormalities (p = 0.001) or SLC2A1 mutations (p = 0.001) but fewer myoclonic features (p = 0.031) and worse seizure‐free survival curve (p = 0.047) than those treated with mono‐ and bitherapy. Children with NP‐EOAE had 2.134 the odds of having relapse during the follow‐up compare to those with P‐EOAE. Significance Children with early onset TAS who did meet Panayiotopoulos's criteria showed a favorable course of epilepsy, whereas patients not fulfilling Panayiotopoulos's criteria showed increased risk of relapse at long‐term follow‐up.